Defining the needs of lung cancer survivors: Physical, social, emotional, and medical needs. Issue 28 (1st October 2022) - Guo, Matthew; Miller, Mattea; Olson, Sarah; Eaton, Cyd; Boulanger, Mary; Turner, Michelle; Hsu, Melinda Laine; Feliciano, Josephine Louella
Abstract : 225 Background: Lung cancer survivors (LCS) are a rapidly growing population. Cancer survivors benefit from dedicated survivorship care, but the physical, psychosocial, and medical needs of LCS are poorly defined. Methods: Non-small cell LCS (defined as alive ≥1 years from diagnosis) of any stage treated at Johns Hopkins were invited to complete an IRB-approved cross-sectional survey of needs of 4 subscales (physical, social, emotional, and medical needs) rated on a 5-point Likert scale (1 = no need, 5 = highest need). Demographic and clinical information were collected by chart review and patient reported questionnaire. Multiple regression models identified factors that were significantly associated with greater total number of needs on each subscale. Results: 235 surveys were completed. We excluded surveys with < 80% completion. Non-Caucasian race was associated with a significantly lower rate of survey completion (p = 0.002). Median age of LCS who completed the survey was 69, most were female (62%), Caucasian (74%), married (71%), or had stage III/IV cancer (60%). More than half of respondents reported emotional needs of fear of recurrence (79%) and living with uncertainty (74%). Common physical needs included fatigue (70%), sleep disturbance (60%), memory and concentration (57%), and weakness (54%). Multivariate analysis identified factors associated with higher needs in physical, social, and emotional needs (Table). We did not identify any factors associated with differences in medical needs. NS – non-significant value. Conclusions: We identified physical, emotional, social, and medical needs that burden survivors of NSCLC. Emotional needs are prevalent. Clinical and demographic factors are independently associated with higher needs in physical, social, and emotional domains. These results are critical in identifying high-impact gaps in providing survivorship care for lung cancer survivors. Future work to identify interventions to address needs is crucial.Clinical and demographic factors independently associated with needs. Characteristic Physical needs Social needs Emotional needs β P value β P value β P value Age ≥ 65 vs < 65 NS NS -3.9 < 0.00 -2.8 .006 Female vs. male NS NS NS NS 2.1 .039 Current / former smoker vs. never NS NS NS NS 2.1 .035 Time since diagnosis 1-2 yrs. Vs. +5 yrs 2-5 yrs vs +5 yrs NS NS 2.7 2.1 .007 .039 NS NS Lines of systemic therapy 1-2 vs. 0 3+ vs 0 2.6 3.1 .01 .003 2.8 .006 NS NS Income < 30, 000 vs +75, 000 30, 000-75, 000 vs > 75, 000 2.0 .04 4.7 3.5 <.001 <.001 NS NS